Natural young oak stands of Left-Bank Forest-Steppe and features of tending felling there by means of mechanized method - Tkach, V. P.; Rumіantsev, M. Н.; Luk’yanets, V. A.; Kobets, O. V. (Forestry and Forest Melioration, 2021)
Introduction Tending felling in young stands is the main forestry practice for growing highly productive and resilient stands. The use of mechanization for tending felling significantly reduces material and labor costs and increases labor efficiency. The aims of the study were to study species composition in natural young stands in oak forest types within the Left-Bank Forest-Steppe, to assess tree species composition in young stands of natural seed origin with a predominance of English oak, to determine the optimal variant of mechanized felling for maximum preservation the main species. Materials and Methods The forest inventory materials were the basis for the calculations. The area of the studied stands was more than 284 thousand hectares (about 70 thousand subcompartments), in particular about 19 thousand hectares of young stands (6.6 thousand subcompartments). Specificities of mechanized cleaning in young stands were studied at a permanent research object of the Laboratory of Forestry of Ukrainian Research Institute of Forestry and Forest Melioration named after G. M. Vysotsky. The experiment was established in 2016 in the forest managed by Kharkiv Forest Research Station (Kharkiv region, Derhachi Forestry). The experiment consisted of four variants (plots); the area of each plot was 0.25 ha. The plot with a young stand after selective cleaning with a Stihl brush cutter served as a control. In other variants, 3-meter-wide corridors were cut through with the use of a rotary corridor cutter RKR-1,5. The corridors were alternated with the unfelled strips of different widths (3, 4.5, and 6 m). Assessment of seedlings and natural regeneration and measuring average height and diameter was carried out on circular plots according to the method developed in URIFFM. Results The young stands of different tree composition in oak forest types within the Left-Bank Forest-Steppe grow at an area of almost 21 thousand hectares (7% of the total area of stands). Naturally originated stands cover 30% of the total area of young stands. The stands of common ash (39%) and Norway maple (32%) are predominant at a young age. The species composition of modal natural young stands with a predominance of English oak is unsatisfactory. In general, in 60% of the area of young stands of natural seed origin and 76% of vegetative origin, the proportion of oak in the stand composition did not exceed 40%. The stands with 80% of oak or more occupy only 8% of the area. Five years after the cleaning (as of September 2021), the number of oak trees in the formed young stands ranged from 4.9 thousand per ha to 7.6 thousand per ha (64.6–67.6% of the total number of trees) depending on the variant. After the mechanized cleaning according to the proposed technology, a young stand was formed at the age of 12 with a composition 65–70% of oak, 25–30% of ash, and 5–10% of Norway maple+lime. Conclusions The largest number of oak trees (6.4 thousand stems per ha) was recorded in the experimental variant where 3-meter-wide corridors were cut through and alternated with unfelled strips of 6 m wide. Such an amount of oak is sufficient to ensure the development of oak stands of natural origin.